2017
DOI: 10.1111/1365-2745.12788
|View full text |Cite
|
Sign up to set email alerts
|

Are mycorrhizal fungi our sustainable saviours? Considerations for achieving food security

Abstract: Summary The 20th century saw dramatic increases in agricultural productivity, largely through the development and application of pesticides, fertilisers rich in nitrogen and phosphorus, and advances in plant breeding and genetic technologies. In the last 15 years, however, many key crop yields have plateaued. Climate change, an ever‐increasing human population, depletion of global rock‐phosphorus and growing energy prices make current fertiliser production unsustainable and represent sizeable challenges to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
172
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(177 citation statements)
references
References 127 publications
(190 reference statements)
2
172
1
2
Order By: Relevance
“…AMF have also been shown to reduce symptoms of arsenic toxicity by improved phosphate nutrition and increased activity of compounds, such as glutathione-S-transferase, which transform arsenic into non-toxic forms [72,73]. AM symbiosis has been shown to reduce assimilation of other adverse heavy metals, such as copper, chromium, cadmium and cobalt [19,36,77]. It has been suggested that altered phosphate transport during AM colonization alleviates symptoms of phosphate toxicity in highly-fertilized soils [76].…”
Section: Positive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF have also been shown to reduce symptoms of arsenic toxicity by improved phosphate nutrition and increased activity of compounds, such as glutathione-S-transferase, which transform arsenic into non-toxic forms [72,73]. AM symbiosis has been shown to reduce assimilation of other adverse heavy metals, such as copper, chromium, cadmium and cobalt [19,36,77]. It has been suggested that altered phosphate transport during AM colonization alleviates symptoms of phosphate toxicity in highly-fertilized soils [76].…”
Section: Positive Effectsmentioning
confidence: 99%
“…AMF may also have potential for phytoremediation [36][37][38]; however, this review focusses on approaches that could be taken by crop breeding rather that adding AMF to soil. [4,[60][61][62][63][64][65][66] Water acquisition [67,68] Zinc acquisition [5,6] Drought tolerance [67,68] Salinity tolerance [29,[69][70][71] Reduced arsenic toxicity [72,73] Reduced sulphur starvation [74,75] Reduced phosphate toxicity [76] Reduced assimilation of adverse heavy metals [19,36,77] Disease resistance Increased resistance to root [31,[78][79][80] and foliar [81][82][83][84][85] pathogens Reduced arbuscular mycorrhizal colonization in mlo mutants [86] Jasmonic acid production [87][88][89][90] Components required for AM colonization used by pathogens, Golovinomyces cichoracerum (DC.) V.P.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the immobility of P in the soil (especially in soils low in available Pi), the ability of a crop to access sufficient P depends on its rooting characteristics and the ability to form relationships with AMF, which effectively act as extensions of the root system (Liu et al, 2003). The AMF symbiosis is well known to assist plants with P uptake (Landry et al, 2008; Thirkell et al, 2017) by reaching beyond the P depletion zone that occurs immediately surrounding roots, allowing greater access to soil P reserves (Bolan, 1991). Arbuscular mycorrhizal fungi have been shown to have a greater P uptake efficiency than plant roots by accessing P at lower soil solution P i concentrations and by taking it up at increased rates (Liu et al, 2007).…”
Section: The Role Of Arbuscular Mycorrhizal Fungimentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi, like plant roots, can take up orthophosphate anions from the soil solution but have also recently been shown to be able to access Po stores via the secretion of acid phosphatases (Sato et al, 2015). Because of AMF's P scavenging and uptake efficiency abilities, there is an interest in managing soil AMF populations to reduce chemical fertilizer use while maintaining crop yield (Bender et al, 2016; Thirkell et al, 2017). …”
Section: The Role Of Arbuscular Mycorrhizal Fungimentioning
confidence: 99%
See 1 more Smart Citation